Spy - Bell, Ted (Bell, Ted. Alex Hawke novel, 2025)
When a mysterious explosion destroys his research vessel in the middle of the Amazon, Alex Hawke is captured by Indigenous cannibals. Before he manages to escape, he learns that a fearsome foe is preparing for war-but against whom?When he regains contact with his American and British intelligence counterparts, Alex's worst fears are confirmed. In the jungle are highly trained Hezbollah warriors who are planning an unspeakably violent jihad against America. While the United States focuses its efforts on the escalating border disputes with Mexico, Alex vows to put a stop to the deadly plot-no matter the cost.